2018
DOI: 10.1016/j.juro.2017.09.077
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Scores are Independent of Disease Volume in Men with Favorable Risk Prostate Cancer: Implications for Choosing Men for Active Surveillance

Abstract: We will provide journalists and editors with full-text copies of the articles in question prior to the embargo date so that stories can be adequately researched and written. The standard embargo time is 12:01 AM ET on that date. Questions regarding embargo should be directed to jumedia@elsevier.com. M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…While this cohort had a higher percentage of IR category cases, the 25% NCCN risk category reclassification rate with the GPS test is similar to previously reported reclassification rates 5,6 . While no significant difference was seen in the percentage of patients in each NCCN risk category change group who underwent prostatectomy, a large number of other factors were used to determine which patients underwent definitive therapy, including UCSF‐CAPRA score, 30 absolute GPS, and imaging findings, which confounds the use of treatment as an outcome measure here.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…While this cohort had a higher percentage of IR category cases, the 25% NCCN risk category reclassification rate with the GPS test is similar to previously reported reclassification rates 5,6 . While no significant difference was seen in the percentage of patients in each NCCN risk category change group who underwent prostatectomy, a large number of other factors were used to determine which patients underwent definitive therapy, including UCSF‐CAPRA score, 30 absolute GPS, and imaging findings, which confounds the use of treatment as an outcome measure here.…”
Section: Discussionsupporting
confidence: 70%
“…It can be argued that GPS is most useful when it results in NCCN risk category reclassification, as this may affect patient management. Previous studies have examined the effect of GPS on NCCN risk category reclassification, with reports showing approximately one‐quarter 5 to one‐third 6 of patients having reclassification upon addition of the test. It is not clear why some cases are reclassified as a result of this molecular testing.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our present finding that pathological upgrading was common regardless of tumour volume is consistent with a recent publication examining the association between disease reclassification by genomic classifiers and biopsy tumour volume. That analysis of men with very-low- and low-risk prostate cancer at diagnosis determined that genomic disease reclassification was independent of biopsy tumour volume [16]. Last, our determination that the frequency of upgrading and adverse pathological features on RP specimens was significantly higher for patients with unreassuring compared to reassuring confirmatory test results highlights that confirmatory test results are providing the patient and physician with valuable and reliable information, and that patients and/or physicians are acting on the confirmatory test results.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published study of a cohort of 296 men with very low-risk (37.8% ) or low-risk (62.2%) disease who underwent GPS testing found that GPS score did not differ significantly across quartiles of disease volume (defined as percent of positive cores, number of cores with > 50% involvement, largest involvement of any single core, and PSA density) [13]. However, the median likelihood of favorable pathology at RP was statistically different between volume quartiles.…”
Section: Prediction Of Disease Progression In Active Surveillancementioning
confidence: 99%